Kemampuan Managerial Dalam Pengambilan Keputusan Yang Efektif - Satar, Safaruddin; Sohiron, Sohiron (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of this research is to analyze managerial abilities in effective decision making. This type of research is qualitative. Data collection by observation and interviews. Data analysis using triangulation. The research results Managerial abilities in effective decision making at SMP Negeri 1 Siantan highlight the important role of managers in ensuring a coordinated and timely decision process. By efficiently utilizing available data and information, managers can direct teams to comprehensively consider various options before deciding on the best course of action to achieve educational goals. Decisions taken by taking into account the aspirations of stakeholders and the needs of students can strengthen the integrity of the school and provide a sustainable positive impact on the development of education in the environment.